Antipsychotic Use and Psychiatric Hospitalization in First-Episode Non-affective Psychosis and Cannabis Use Disorder: A Swedish Nationwide Cohort Study - Denissoff, Alexander; Taipale, Heidi; Tiihonen, Jari; Di Forti, Marta; Mittendorfer-Rutz, Ellenor; Tanskanen, Antti; Mustonen, Antti; Niemelä, Solja (Oxford University Press, 2025)
Background and Hypothesis
There is a paucity of research on treatment outcomes of patients with psychosis and cannabis use disorder (CUD). We aimed to compare the effectiveness of antipsychotics in reducing the risk of hospitalization in patients with first-episode psychosis (FEP) and co-occurring CUD.
Study Design
We utilized a nationwide Swedish cohort of patients with longitudinal register data from the year 2006 to 2021. Participants were patients with FEP and co-occurring CUD (n = 1820, 84.73% men, mean age 26.80 years, SD 8.25 years). The main outcome was hospitalization due to psychotic relapse. Hospitalization due to any psychiatric disorder or substance use disorder (SUD) were examined as secondary outcomes. Within-individual Cox regression models were used to study these associations.
Study Results
Use of any antipsychotic was associated with a 33% risk reduction of psychotic relapse (aHR = 0.67; 95% CI 0.60–0.75). Clozapine (0.43; 0.29–0.64), long-acting injectable (LAI) formulations of risperidone (0.40; 0.22–0.71), aripiprazole (0.42; 0.27–0.65), and paliperidone (0.46; 0.30–0.69) were associated with the lowest risk of relapse. The association between the LAI formulation of olanzapine and hospitalization due to psychosis was statistically non-significant (0.61; 0.35–1.05). Clozapine was associated with an 86% risk reduction of hospitalization due to SUD (0.14; 0.05–0.44). Of oral non-clozapine antipsychotics, aripiprazole was associated with the lowest risk of hospitalization due to psychotic relapse (0.61; 0.45–0.83).
Conclusions
These findings support the use of clozapine, LAI formulations of second-generation antipsychotics other than olanzapine, or oral aripiprazole to prevent hospitalization in FEP and co-occurring CUD.